Frankie vs the Pirate Pillagers - Lampard, Frank (London : Little, Brown Books For Young Readers, 2015)
"Frankie and his team love playing football. There's always time for a game. But when they win an old football at a carnival, they're going to be transported to a magical world of football they never knew existed! Can Frankie and his team beat the Pirate Pillagers and make their way home?"--Cover.
Keywords: Pirates -- Juvenile fiction; Fantasy fiction